Proceedings of Eurosensors 2017, Paris, France, 3–6 September 2017 2017
DOI: 10.3390/proceedings1040576
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Temperature and Strain on Power Conversion Efficiency of PVDF-Based Thermal Energy Harvesters

Abstract: There can be a significant discrepancy between predicted and measured power conversion efficiency when using piezoelectric polymers for thermal energy harvesting. The influence of temperature and strain on electrical parameters can impact overall performances. We report the temperature and strain dependence of PVDF dielectric constant and losses and their impact on power conversion efficiency of composite thermal SMA-PVDF energy harvesters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…The conversion efficiency of the PVDF transducer with the 1.66 F output super capacitor array now lies in the range between 2.7-4.2 %. These efficiency levels agree with the above approximate calculation and agree with what is usually reported in the literature [47,192,197,198]. However, the experiments are usually performed with microFarad capacitors, or resistive circuits and -as already discussed, definitions of efficiency vary between research groups [181].…”
Section: Beam Curvature Measurements Processing and Efficiency Calculationssupporting
confidence: 87%
See 1 more Smart Citation
“…The conversion efficiency of the PVDF transducer with the 1.66 F output super capacitor array now lies in the range between 2.7-4.2 %. These efficiency levels agree with the above approximate calculation and agree with what is usually reported in the literature [47,192,197,198]. However, the experiments are usually performed with microFarad capacitors, or resistive circuits and -as already discussed, definitions of efficiency vary between research groups [181].…”
Section: Beam Curvature Measurements Processing and Efficiency Calculationssupporting
confidence: 87%
“…According to Chang et al [191], the early onset of the nonlinear domain wall motions behavior has been identified as one mechanism responsible for the apparent high piezoelectricity measured in nanofibers of PVDF. Also, Bernard et al [192], found significant discrepancy between predicted and measured power conversion efficiency when using PVDF for thermal energy harvesting. Kim et al [193] studied nanosheet-based piezoelectric nanogenerator with different thicknesses and types of dielectric layers and demonstrated that a careful design of the dielectric layer is necessary to improve the electrical outputs of piezoelectric nanogenerators [194,195].…”
Section: Beam Curvature Measurements Processing and Efficiency Calculationsmentioning
confidence: 99%
“…Though, in this study, all experiments were conducted in ambient temperature, the efficiency of power generation can be impacted by the change in temperature. For instance, a recent study by Bernard et al [26] reported the increase of dielectric constant of the PVDF with the increase of temperature from 30 • C to 60 • C and strain up to 2.5%, which caused a decrease in efficiency down to 60-75%, as opposed to ideal conversion efficiency of 90%. They suggested that the circuit output capacitance must be decreased in proportion to be adapted to operation conditions in order to restore higher power generation capacity.…”
mentioning
confidence: 99%